MHD boundary layer behaviour over a moving surface in a nanofluid under the influence of convective boundary conditions - Abdel-wahed, Mohamed (Strojniški vestnik, 2017)
The present work provides an analysis of the hydro-magnetic nanofluid boundary layer over a moving surface with variable thickness in the presence of nonlinear thermal radiation and convective boundary conditions. The governing partial differential equations system that describes the problem is converted to a system of ordinary differential equations by the similarity transformation method; such a system is solved numerically. The velocity, temperature, and nanoparticle concentration of the boundary layer are plotted and investigated in details. Moreover, the surface skin friction, rate of heat and mass transfer are deduced and explained in detail.
Keywords: konvektivni pogoji; MHD tok; nanofluidi; nanotekočine; nelinearno toplotno sevanje